Clinical, microbiological and therapeutic aspects of vulvovaginal candidiasis and recurrent vulvovaginal candidiasis: importance of regional surveys - Rodrigues, Márcio Tavares; Simões, Letícia Zambelli; Diniz, Cláudio Galuppo (HU Revista, 2010)
Vulvovaginal candidiasis (VVC) has a varied aetiology. The yeasts involved in this disease have presented increased resistance to the azoles and poliens, the drugs of choice for treatment. In recurrent VVC, the therapeutic difficulties are even greater. The epidemiological relevance of aetiological diagnosis and of the antifungigram in clinical treatment is discussed.